Distribution of calcareous nannofossils in sediments cores in the western South Atlantic - Sherwood W Wise; Elena L Mostajo (PANGAEA, 1983)
Calcareous nannofossil assemblages recovered in four Islas Orcadas piston cores along the northern margin of the Maurice Ewing Bank on the eastern Falkland Plateau are correlated with lower Oligocene and middle Eocene sections at Deep Sea Drilling Project Sites 511 and 512, respectively. Results indicate that the Paleogene section near the piston core stations is generally more calcareous and complete than at the Leg 71 drill sites and could provide a valuable highlatitude biostratigraphic reference locality if drilled at some future date.